INVESTIGATION OF FACTORS RELATING TO THE CHANGE OF CYCLE THRESHOLD (CT) INDEX IN RT-PCR TESTING AMONG COVID-19 PATIENTS, AT THE MILITARY HOSPITAL 7 - Hoang Van Ly; Nguyen Huu Mai; Tran Van Hai; Ngo Nhat Tan; Dao Van Hoan; Nghiem Thi Hiep (Tạp chí Y học Quân sự, 2023)
Purpose: We aimed to evaluate some factors related to changes of CT values in RT-PCR testing among patients infected with COVID-19 treated at Military Hosptial 7, Military Zone 3. This contributes to diagnosis and prognosis of disease. Methods: Prospective and cross-sectional descriptive study. Results: The mean age of the patients was 40.06 ± 14.34 years. 80.46% were males. 97.39% of the patients were vaccinated against COVID-19. 60.58% of them experienced post-COVID-19 syndrome. - On day 5 of COVID-19, the significantly lower CT values found in individuals reporting receipt less than 3 doses with respect to those who received completely 3 doses of COVID-19 vaccines (OR = 1.59; p < 0.05). Patients developing post-COVID-19 syndrome had a lower CT value than those without manifestations of this syndrome (OR = 1.73; p < 0.05); subjects treated with antiretroviral drugs (ARV) had a higher CT value than those nontreated (with OR = 5.06; p < 0.001). - On day 10 of COVID-19, subjects without antiretroviral drugs (ARV) use had a lower CT values than those on antiretroviral medications (OR = 3.91; p < 0.001).